Набутки чину св. Василя Великого в освітньо- виховній галузі та ставлення до них російського самодержавства наприкінці ХVІІІ – в першій третині ХІХ століття. - Шеретюк, Р.М. (Відділення релігієзнавства Інституту філософії ім. Г.С. Сковороди НАН України, 2010)
У статті Руслани Шеретюк досліджено основні вектори освітньо- виховної діяльності Чину святого Василія Великого (ЧСВВ), вплив на неї геополітичних трансформацій, пов’язаних з поділами Польщі, з’ясовано причини, механізми та наслідки поступової ліквідації василіанських освітніх осередків. Ключові слова: Уніатська церква, Чин святого Василія Великого, василіани, василіанські студії, новіціати, новіції (новики), семінарії, колегії, парафіяльні школи. В статье Р. Шеретюк «Достояния Чина святого Василия Великого в образовательно-воспитательной отрасли и отношение к ним российского самодержавия в конце ХVIII – первой трети ХIХ в.» исследовано основные векторы образовательно-воспитательной деятельности Чина святого Василия Великого (ЧСВВ), влияние на нее геополитических трансформаций, связанных с разделами Польши, раскрыты причины, механизмы и последствия постепенной ликвидации василианских образовательных центров. Ключевые слова: Униатская церковь, Чин святого Василия Великого, василиане, василианские студии, новициаты, новиции (новики), семинарии, коллегии, приходские школы. Ruslana Sheretyuk: The possessions of the rank of Saint Vasyliy the Great in the educational sphere and the attitude of Russian autocracy to them at the and of 18th century – the first of the third part of the 19th century. The article under the title «The possessions of the rank of Saint Vasyliy the Great in the educational sphere and the attitude of Russian autocracy to them at the and of 18th century – the first of the third part of the 19th century» written by Ruslana Sheretyuk examined the main vectors of educational activity of the rank of Saint Vasyliy the Great and the effect of geopolitical transformations which are connected with the allotment of Poland on it; cleared up the reasons, the works and the results of gradual elimination of Vasylian educational centres. Keywords: the Uniat Church, the rank of Saint Vasyliy the Great, Vasylians, Vasylian schools, noveltists, novelties, seminaries, collegias, parish churches.